Pengembangan Model Kepemimpinan Perberdaya di Lingkungan Birokrasi - Anwaruddin, Awang (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2006)
Various crisis in the fields of economy, social, and public service has attacked Indonesia since the last decade without strategic solutions as expected the society. Such condition represents one of indicators of bureaucracy incapability in anticipacing and handling the global problems as the signs of global ‘disaster’ have been indicated since 1990s. As we know, Osborne and Patrick (1997) wrote in their phenomenal book ‘Banishing Bureaucracy’ that the recent world had been characterized by rapid change, technological revolution, global economic competition, demassified markets, educated workforces, demanding customers, and severe fiscal. Thus, a strategic solution should be formulated, among others, by transforming the traditional bureaucracy leadership to be empowerment one. Through this leadership approach, it is expected that the profile of Indonesian bureaucracy will be characterized by creativities and inovations to solve the global problems.